Length–weight relationships for three fish species from Yalong River in China. (17th October 2013) - Zhang, J.‐B.; Cao, J.‐F.; Yang, X.‐F.; Yang, R.‐B.
Summary This study provides the first report of length–weight relationships (LWRs) for three fish species collected from the Yalong River, one of the tributaries to the upper reaches of the Yangtze River, China. The LWRs of these fish species were BW = 0.0070TL3.0539 (r2 = 0.9662) for Schizothorax wangchiachii, BW=0.0134TL2.8523 (r2 = 0.9676) for Schizopygopsis malacanthus, and BW=0.0143TL2.9253 (r2 = 0.8538) for Euchiloglanis kishinouyei, respectively. Also investigated were the spawning season, absolute fecundity and main food items of the three fish species in the natural environment. In addition, new maximum sizes for the three species are provided.